Radiation as an Immune Modulator: Where We Are With Modern Total Body Irradiation - Simiele, Eric; Dandapani, Savita; Han, Chunhui; Wong, Jeffrey; Hiniker, Susan M.; Kovalchuk, Nataliya (Seminars in radiation oncology, 2025)
Total body irradiation (TBI) has been an important component of myeloablative and nonmyeloablative conditioning regimens for allogeneic hematopoietic stem cell transplantation (HSCT) for decades. Playing a dual role, both cytotoxic and immuno-suppressive, TBI eliminates residual disease while also impairing the immune system from rejecting the foreign donor cells being transplanted. Unlike chemotherapy, radiotherapy is not hampered by perfusion, diffusion, or the blood-barrier effect and can effectively treat sanctuary sites. However, radiotherapy is subject to radiobiological trade-offs between destroying cancer cells, preserving immune and hematopoietic stem cells, and causing various adverse effects in normal tissue. Optimizing the immuno- suppressive effect of fractionated TBI while sparing normal organs requires careful consideration of total dose, dose per fraction, dose rate, target dose coverage, and dose to organs. Prospective multi-institutional trials are required to elucidate this matter further. However, as various recent surveys across the world indicate, the heterogeneity of 2D TBI practices, inaccurate dose calculation and dosimetry, and differences in reporting across institutions makes conducting these multi-institutional studies of TBI challenging. Technological advancements in radiotherapy planning and delivery are prompting a transition to modern intensity modulated techniques such as Volumetric Modulated Arc Therapy (VMAT) TBI and helical TomoTherapyTM TBI, which can better spare normal organs and potentially reduce radiotherapy-related toxicities without compromising TBI effectiveness. This review discusses the present developments and outcomes and toxicity for modern TBI techniques as well as total marrow irradiation (TMI), and total marrow and lymphoid irradiation (TMLI).